A revision of the genus Omalium Gravenhorst, 1802 (Coleoptera: Staphylinidae: Omaliinae) of the Himalayan region - Shavrin, Alexey V. (Zootaxa, 2023)
Five species groups are established for 18 species of the genus Omalium Gravenhorst, 1802 from the Himalayan region: Acutangulum group containing O. acutangulum sp. n. (central Nepal) and O. amicorum sp. n. (Nepal); Amplissimum group containing O. amplissimum sp. n. (eastern Nepal) and O. bilobum sp. n. (eastern Nepal); Caesum group containing Palaearctic O. littorale Kraatz, 1857 and O. humerale Cameron, 1924 (India: Uttarakhand); Oxyacanthae group containing O. alticola Cameron, 1941 (India: Kashmir, Uttarakhand; western Nepal), O. altivagans Bernhauer, 1915 (India: Kashmir), O. beesoni Cameron, 1924 (India: Uttarkhand; western Nepal) O. marginatum Cameron, 1941 (India: Kashmir, Punjab; eastern Nepal), O. scapulare Coiffait, 1982 (India: West Bengal; western Nepal); Rivulare group containing O. angustissimum sp. n. (central Nepal), O. cariosum Cameron, 1924 (India: Uttarakhand), O. flavotestaceum sp. n. (India: West Bengal; eastern Nepal), O. kumari sp. n. (western Nepal), O. latocavum sp. n. (central Nepal), O. nigrum Coiffait, 1982 (Nepal) and O. secretum Cameron, 1924 (India: Uttarakhand; Nepal). Each species group is briefly discussed and keyed. Species in each group are (re-) described, illustrated, and their geographical distributions are mapped. Three synonyms are established: O. alticola = O. monticola Cameron, 1941 syn. n., O. beesoni = O. parallelicollis Coiffait, 1982 syn. n., O. littorale = O. gartneri Coiffait, 1982 syn. n. Lectotypes are designated for O. (s. str.) beesoni, O. (s. str.) cariosum, O. (s. str.) humerale and O. (s. str.) secretum. Additional material on O. littorale from Middle Asia is provided. Several species of the genus are recorded for the first time from certain areas: O. alticola for Uttarakhand (India) and Nepal, O. littorale for Pakistan, O. marginatum for Punjab (India) and Nepal, O. scapulare for India (Uttarakhand, West Bengal), and O. secretum for Uttarakhand (India).